Anomalous anatomical variation in extrahepatic biliary tree and pancreas and its related vessels: a cadaveric study - Koshariya, Mahim; Behram, Sheikh; Singour, Jay Prakash; Tiwari, Shashikant; Khare, Vidhu (International Surgery Journal, 2019)
Background: Congenital anamolies of extrahepatic biliary apparatus and pancreas have long been recognized and are of clinical importance because when present may surprise the surgeon during surgery and lead to iatrogenic injuries. Surgeries on extra-hepatic biliary apparatus and pancreas are regularly performed throughout the world. Thus insight into the normal anatomy and congenital variations will reduce complication and definitely improve outcome. Methods: Study was conducted in department of surgery GMC Bhopal and dissection was carried out in Department of Forensic Medicine on 100 cadavers with approval from ethical committee. Results: In 100 cases 70 were male and 30 female. The most common variation in extra hepatic biliary apparatus was short cystic duct was found in 6% cases then formation of common hepatic duct by union of right hepatic duct and left hepatic duct was intrahepatic in 3% cases. There was low insertion of cystic duct with common hepatic duct in 1% case. Cystic artery originating from left hepatic artery in 1% case, in 1% case cystic artery was anterior to common hepatic duct. In Pancreas anterior arterial arcade was absent in 2% cases and its origin varied in 2% case. Posterior pancreatic arcade absent in 1% cases and variation in origin was present in 1% case. The variation in pancreatic duct course was present in 22% cases. Conclusions: Thus significant variation was seen and it could definitely be helpful to hepatobiliary, laproscopic surgeons, radiologist and will further contribute to literature on variation of extrahepatic biliary apparatus and pancreas and its related vessels.